Legal Protection for Victims in Fake Investment on Telegram - Zeno Eronu Zalukhu; Yasmirah Mandasari Saragih; Fauzan Fauzan (International Forum of Researchers and Lecturers, 2025)
The Unitary State of the Republic of Indonesia is a country of law that guarantees justice and protection for its citizens. This protection is stated in the 1945 Constitution Article 28G paragraph (1), namely: